Advances in Intelligent Systems and Interactive Applications Proceedings of the 2nd International Conference on Intelligent and Interactive Systems and Applications (IISA2017) - Xhafa, Fatos; Patnaik, Srikanta; Zomaya, Albert Y.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents research papers from diverse areas on novel Intelligent Systems and Interactive Systems and Applications. It gathers selected research papers presented at the 2nd International Conference on Intelligent and Interactive Systems and Applications (IISA2017), which was held on June 17-18, 2017 in Beijing, China. Interactive Intelligent Systems (IIS) are systems that interact with human beings, media or virtual agents in intelligent computing environments. The emergence of Big Data and the Internet of Things have now opened new opportunities in both academic and industrial research for the successful design and development of intelligent interactive systems. This book explores how novel interactive systems can be used to overcome various challenges and limitations previously encountered by human beings by combining machine learning algorithms and the analysis of recent trends. The book presents 125 contributions, which have been categorized into sevensections, namely: i) Autonomous Systems; ii) Pattern Recognition and Vision Systems; iii) E-Enabled Systems; iv) Mobile Computing and Intelligent Networking; v) Internet and Cloud Computing; vi) Intelligent Systems, and vii) Various Applications. It not only offers readers extensive theoretical information on Intelligent and Interactive Systems, but also introduces them to various applications in different domains.
A PROUD methodology for TOGAF business architecture modeling -- Application of SVM Based on Information Entropy in Intrusion Detection -- Research of Music Recommendation System Based on User Behavior Analysis and Word2vec User Emotion Extraction.-Exploration of Information Security Education of University Students -- Part 4. Mobile and Wireless Comm. -- Research on the path monitoring capability of wireless multimedia sensor network -- Preopen set and preclosed set on intuitive fuzzy topological spaces -- Neural Network method for Compressed Sensing -- A Survey on Microwave Surface Emissivity Retrieval Methods -- Design of Multi-mode Switching Damping Shock Absorber for Active Suspension and Ride Comfort Test -- Research on the System of Patrol Unmanned Aerial Vehicle (UAV) Docking on Charging Pile based on Autonomous Identification and Tracking -- On Data Analysis in Forest Fire Induced Breakdown of the Transmission Line -- Ultrasonic Guided Wave Testing Method of Gun Barrel Crack Defects Basedon L (0, 2) Mode -- Target re-identification based on dictionary learning -- Research on High Impedance Fault Detection Method of Distribution Network Based on S Transform -- Research on the protocols of VPN -- Penetration Level Permission of Small Hydropower Station in Distributed Network -- Research on Smooth Switching Method of Micro-Grid Operation -- A new BDD algorithm for fault tree analysis -- A sparse nonlinear signal reconstruction algorithm in the wireless sensor network -- Chinese POS Tagging with Attention-based Long Short-Term Memory Network -- A New Weighted Decision Making Method for Accurate Sound Source Localization -- The efficiency factors of point-to-point wireless energy transfer system in a closed satellite cavity -- Personalized Point-of-Interest Recommendation in Location-Based Social Networks -- Verification of CAN-BUS Communication on robots based on xMAS -- Network Traffic Classification Using Machine Learning Algorithms -- Fault analysis and fault diagnosis method reviewon active distribution network -- Extensive Survey on Networked Wireless Control -- Part 5. Internet and Cloud Computing -- Research and Design of Smart Home System Based on Cloud Computing -- Website Structure Optimization Based on BS Matrix -- The Effects of Bank Employees' Information Security Awareness on Performance of Information Security Governance.-"A Comparative Study on Agglomeration Effects of the Central Cities of Three Urban Agglomerations in China.--- A Case Study of Producer Services" -- Part 6. Intelligent Systems -- A Dynamic Node's Trust Level Detection Scheme for Intelligent Transportation System -- An application of  Multi-Objective Genetic Algorithm based on Crossover Limited -- An Method for Extracting Objects in Physics Using Unit Semantic Model -- A novel matching technique for two-sided paper fragments reassembly -- An improved memetic algorithm with novel level comparison for constrained optimization -- FPGA based Real-time Processing Architecture for Recurrent Neural Network -- Publication Recommendations of Manuscripts Using Improved C4.5 Decision Tree Algorithm -- Design Replica Consistency Maintenance Policy for the Oil and Gas Pipeline Clouding SCADA Multiple Data Centers Storage System -- SPSS-based Research on Language Learning Strategy Use.-Study on intelligent monitoring of power transformer based on FPGA -- Mutual Fund Performance Analysis using Nature Inspired Optimization Techniques: A Critical Review -- Part 7. Others -- Synthesis Algorithm Based on the Pre-evaluation of Quantum Circuits for Linear Nearest Neighbor Architectures -- Study of an SIR epidemic disease model with special nonlinear incidence and computer simulation -- An Improvement Response Surface Method based on Weighted Regression for Reliability Analysis -- The Greedy Algorithm and its Performance Guarantees for Solving Maximization of Submodular Function -- Model of Evaluation on Quality of Graduates from Agricultural University Based on Factor Analysis -- Distributed CollaborativeControl Model Based on Improved Contract Net -- K Distribution Clutter Modeling Based on Chebyshev Filter -- Influence of Liquid Film Thickness on Dynamic Property of Magnetic-Liquid Double Suspension Bearing -- Characteristics Analysis on Open-type Liquid Hydrostatic Guideway with Unequal Area Oil Pocket -- Influence of Liquid Film Thickness on Static Property of Magnetic-Liquid Double Suspension Bearing -- The Research on the Thinking of Large Data for Agricultural Products Market Consumption in Beijing -- The application of decision tree in workow -- Constructing and analysis of the state spaces of workflow process models -- Analysis on the causes of bad PCBA heavy tin -- Characteristics of solder paste and reflow process analysis.-Design and Implementation of ARM7 Instruction Set Based on GDB Framework -- Simulation and Research on the Rotor Flux Linkage Model of Asynchronous Motor -- Application of Fuzzy PID Control for Oil Temperature in Overvoltage Withstand Test -- Study on High Overload Characteristics of Ultrasonic Electric Actuator.-Design and analysis of resonator for the resonant accelerometer -- Analysis on Quality and Safety of Toys for Children -based on the survey data of Beijing.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence